Novel, smart and RFID assisted critical temperature indicator for supply chain monitoring. (January 2017) - Lorite, Gabriela Simone; Selkälä, Tuula; Sipola, Teemu; Palenzuela, Jesús; Jubete, Elena; Viñuales, Ana; Cabañero, Germán; Grande, Hans J.; Tuominen, Jarkko; Uusitalo, Sanna; Hakalahti, Leena; Kordas, Krisztian; et al.
Abstract: In order to reduce food waste and meet the needs of the demanding modern consumer regarding the quality of food items, it is crucial to monitor the supply chain and storage conditions of perishable food products. Considering this scenario, temperature plays an important role on food safety and quality during storage and supply. In this work, a critical temperature indicator (CTI) based on a solvent melting point is developed. Furthermore, the present CTI working principle is improved by the use of microfluidics technology. As final result, a novel and functional CTI-smart sensor which combines irreversible visual color changes and radio frequency identification (RFID) technologies is achieved. Such CTI integrated to a RFID tag provides a unique advantage to monitor the supply chain in real time by the simple use of a RFID reader in strategic points. Highlights: We present the development of a critical temperature indicator (CTI) integrated with RFID. It is based on the melting point of a specific solvent. Several different designs were demonstrated. A final CTI design within clear visual response is proposed based on microfluidics. The CTI-smart sensor presents fast response to the critical temperature of 18–19 °C.